What use is a moose? - Waddell, Martin; Robins, Arthur (New York : Scholastic, 1996)
When Jack's efforts to find a use for the moose he has brought home end in disaster, Jack's mother says the moose has to go--until she realizes that being loved is the best use of all.
Keywords: Moose -- Fiction; Pets -- Fiction